ʺProfessional training of future technicians from the research of the production of flour products with suspension nano additiveʺ - Nikulin , A. (Problems of Engineer-Pedagogical Education, 2024)
The article highlights the relevance of the research problem, which is related to the intensive development of innovative technologies in the food industry, the modernization of production and the expansion of the geographical space of domestic cooking, which necessitates radical changes in the process of professional training of specialists in Ukraine. As a result, the modern educational institution should be modernized in accordance with the new paradigm of domestic education and new variable models of professional training of future technicians-technologists should be introduced, in particular for the production of flour products with a suspension nano additive. In previous studies, it was established that suspension nanoadditive (SND) to food products leads to a comprehensive improvement of their consumption and functional-technological properties. So, in particular, CIS nanoparticles have bacteriostatic and antioxidant properties, contribute to better digestion of protein components of food, have a moisture-, fat-retaining and fat-emulsifying effect, are a source of easily digestible iron, and have a beneficial effect on metabolic processes. It has been confirmed that the study of chemical and biological disciplines ensures the formation of knowledge about the regularities of physico-chemical processes during food preparation, the influence of organic and inorganic compounds on the organoleptic and nutritional properties of products, and also contributes to the formation of intellectual abilities of students, activation of cognitive activity and independence, development creative abilities, communication skills, that is, it helps to create a basis for acquiring professional competences, the ability for further productive professional activity. The promising areas of scientific research are the implementation of the author's integrative technology for the study of the production of flour products with a suspension nano-additive for the professional training of future technicians-technologists for the production of food products; to develop a set of special professional, general professional, general scientific, instrumental and social-personal competencies, which are the fundamental basis of professional training of future technicians-technologists for the production of food products.